Multimodales Erzählen in der Orchesterprobe - Messner, Monika (Linguistik Online, 2020)
The focus of attention in this contribution are narrative sequences in orchestra rehearsals realized by the conductor using different semiotic resources such as talk, gesture, facial expressions, gaze and body movement. Adopting a conversation analytic approach to a video-recorded orchestra rehearsal, the article aims to illustrate how narrative elements are implemented in the primarily instructive context of the rehearsal and which functions such narrations fulfil (i. e. joke, argumentation etc.). It will be demonstrated how storytelling is started, unfolded and brought to an end under sequential and multimodal conditions. The analysis also considers how the musicians react to the conductor’s narrations – through gaze, facial expressions and talk – and how they contribute as listeners to the production of narratives. The findings show that the conductor as the narrator and the musicians as his audience organize narrating in orchestra rehearsals in an interactive, multimodal and sequential way.